LEGAL INTERPRETATION OF DIRECTORATE GENERAL OF IMMIGRATION DECREE NUMBER IMI-0352.GR.02.07 OF 2016 CONCERNING THE HANDLING OF ILLEGAL IMMIGRANTS THAT SELF DECLARED AS AN ASYLUM SEEKERS OR REFUGEES IN IMMIGRATIVE SELECTIVE POLICY: HIERARCHY THEORY OF LEGAL - M. Alvi Syahrin; Brianta Petra Ginting (Jurnal Ilmiah Kajian Keimigrasian, 2019)
Displacement is a form of population movement that has different characteristics than other forms of population movement. The movement of population, both in the national territory and those that have crossed national borders, is an event that has long existed in human history and is increasingly happening now. The increasing number of asylum seekers and refugees to the territory of Indonesia, has caused social disturbances, political security, and even order in the community. The number of their arrival is not proportional to the completion rate or placement to the recipient country (Australia). To deal with the problem of asylum seekers and refugees entering and residing in the territory of Indonesia, the government issued a Director General of Immigration Decree Number: IMI-0352.GR.02.07 of 2016 concerning the Handling of Illegal Immigrants who Self Declare as Asylum Seekers and Refugees. This regulation not only affirms Indonesia's position in favor of refugee humanitarian policies, but also makes it incompatible with the legal principles of establishing legislation. The formulation of the problem examined in this paper is how the legal position of Director General of Immigration Decree in the immigration selective policy with a hierarchical theory approach to legal norms. The research method used is normative legal research that is qualitative in nature with mixed logic (deductive and inductive). From the results of the study can be known several legal facts as follows. The legal status of Director General of Immigration Decree Number: IMI-0352.GR.02.07 in 2016 creates disharmony in the legal order (immigration) in Indonesia. Article 7 of Law Number 12 of 2011 has established a sequence of laws and regulations which form the basis for the implementation of all legal regulations in Indonesia. The provisions of this article are in line with the Hierarchical Theory of Legal Norms (Hans Kelsen) which explains that lower norms, valid, sourced and based on higher norms. However, this theory is not negated in the formation of these regulations, where in the body the norms conflict with each other with higher legal norms above. The existence of this regulation has created norm conflicts that lead to the absence of legal certainty. As for the higher regulations that contradict these regulations are as follows: The 1945 Constitution of the Republic of Indonesia, Law Number 6 of 2011 concerning Immigration, Government Regulation Number 31 of 2013 concerning Regulations for Implementing Law Number 6 of 2011 concerning Immigration, and Regulation of the Minister of Law and Human Rights Number M.HH-11.OT.01.01 of 2009 concerning Organization and Work Procedures of Immigration Detention Houses. Conflicting legal norms include: Definition of Detention Center, Determinant Definition, Refugee Handling, UNHCR and IOM Authority in Refugee Handling, Discovery, Collection, Immigration Oversight, Funding, and Sanctions.